Kapitalisasi Tubuh Perempuan - Nurani, Shinta (IAIN Pekalongan, 2017)
The female’s body is something that very dangerous if it is not controlled. Different views of stereotypes and negative labels are given to women. In fact, women serve as commodities and a capitalist political instrument through beauty and sexuality often addressed to women and occur under the hegemony and dominance of certain rulers who are to control commodities and politicization over the female’s body. The correlation of female's body control with their environment raises a women's movement in need of religion in which all activities and movements of women must be based on several alternatives of life ethics that must be held like having to cover ‘aurat’, while working in a safe environment, and others. If the respectable women are able to survive and understand the feminine authenticity of the self as a counterweight to the masculinity that has been produced in general and all areas of public life.